Ecological High Performance Concrete. (2017) - Kubissa, Wojciech; Simon, Tamás; Jaskulski, Roman; Reiterman, Pavel; Supera, Marcin
Abstract: In this paper the authors present the possibility to utilize two waste materials to produce high performance concrete (HPC). To prepare the mixes, Recycled Concrete Aggregate (RCA) of 4-16 mm fraction and Class F fly ash (from coal burning power plant) were used. Concretes with RCA were mixed with 300 kg/m3 of different types of cements and Supplementary Cementing Materials (SCM). The concrete sample specimens were tested for mechanical properties and for some properties which are related to durability. After 28 days compressive strength values up to 59.5 MPa and after 90 days 71.8 MPa were achieved. Besides we obtained good values regarding those properties, which significantly influence the durability of reinforced concrete structures.